Legal Analysis of CSR Practices on Community Welfare in the Textile Industry: Analisis Hukum Praktik CSR terhadap Kesejahteraan Masyarakat di Industri Tekstil - Yosie Saputri, Maharani Octavia; Suharto, Achmad; Taufiqurohman, A. H. As’ari; Aulia, Aulia; Wibowo, Dwi Edi (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Corporate Social Responsibility (CSR) is integral to sustainable economic development and improving community welfare through responsible corporate engagement with stakeholders and the environment. Specific Background: The application of CSR varies significantly across different industrial sectors, influenced by local regulations and company-specific challenges. Knowledge Gap: Comprehensive analysis on the legal aspects and practical implications of CSR in specific industries, such as textile manufacturing, remains limited. Aims: This study aims to evaluate the legal frameworks governing CSR and their impact on community welfare within the textile industry. Results: Findings reveal effective integration of CSR, with a focus on education, health, and environmental sustainability, aligning with legal standards of transparency and accountability. Novelty: The research provides a focused analysis on legal CSR mandates within the textile sector, highlighting specific corporate practices and compliance. Implications: The study highlights the necessity of aligning corporate strategies with legal and ethical standards to enhance social and environmental wellbeing, suggesting more equitable CSR implementation across industries. Highlights: Legal Compliance: Adherence to CSR laws ensuring transparency and accountability. Community Impact: Effectiveness of CSR in improving local welfare, especially in education and health. Sustainability Practices: Integration of environmental sustainability in corporate strategies. Keywords: Corporate Social Responsibility, Community Welfare, Transparency, Accountability